Late Pleistocene and Holocene palaeoenvironmental changes in central Tierra del Fuego (~54°S) inferred from pollen analysis - Musotto, Lorena Laura (2015)
A palynological record was obtained from a coring site in La Correntina mire (54°33´S, 66°59´W, 206 m a.s.l.) in the east of Lago Fagnano, centre of Tierra del Fuego. The pollen record indicates that the valley bottom was ice free shortly before 15400 cal BP. Pioneer vegetation included dwarf shrub heaths, grasses, and herbs with sparsely distributed Nothofagus trees, indicative of dry conditions. Nothofagus expanded by 10000 cal BP, and the forest-steppe ecotone was established by 9400 cal BP implying warmth conditions and increase in available moisture. After ca. 5000 cal BP, the development of a closed-canopy forest is interpreted as wetter and colder conditions. After 3000 cal BP, Nothofagus forest became more open, and by about 400 cal BP a further decline of the forest occurred. A closed-canopy Nothofagus forest re-established after 400 cal BP.